2014
DOI: 10.1513/annalsats.201309-325oc
|View full text |Cite
|
Sign up to set email alerts
|

Sleep-disordered Breathing in Children with Cardiomyopathy

Abstract: Sleep-disordered breathing is common in children with cardiomyopathy. In our present study, 24% of participants exhibited primarily central sleep apnea. The severity of cardiac dysfunction, as measured by left ventricular end diastolic volume index and left ventricular end systolic volume index, is associated with central sleep apnea. Longitudinal research is necessary to better characterize sleep disorders and their impact on cardiac function in a large pediatric cardiomyopathy population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…We found that OSA was common in children with CHD, with an incidence of 57% in our sample, compared with a typical community prevalence of 1% to 5% in children. 25 Additionally, although central sleep apnea has been found to be common in children with cardiomyopathies 26 and adults with heart failure, 27,28 we found no cases of central sleep apnea in this sample of children with CHD. Similarly, we found no cases of nocturnal hypoxemia in our sample.…”
Section: Discussionmentioning
confidence: 55%
“…We found that OSA was common in children with CHD, with an incidence of 57% in our sample, compared with a typical community prevalence of 1% to 5% in children. 25 Additionally, although central sleep apnea has been found to be common in children with cardiomyopathies 26 and adults with heart failure, 27,28 we found no cases of central sleep apnea in this sample of children with CHD. Similarly, we found no cases of nocturnal hypoxemia in our sample.…”
Section: Discussionmentioning
confidence: 55%
“…has been observed in both adult and pediatric populations. Among the pediatric population, a pilot study [17] with overnight polysomnography (PSG) showed that 48% of 21 patients had SDB. Among these, 24% had central sleep apnea (CSA) while the remaining had OSA.…”
Section: Prevalence Of Sleep Disordered Breathing (Sdb) In Hypertrophmentioning
confidence: 99%
“…Medical therapy had included Digoxin, Carvedilol, Ramipril, and Spironolactone. He underwent a standard PSG according to international guidelines at the time of admission that was part of a prospective observational study to describe sleep disordered breathing (SDB) in children with known cardiomyopathy, the group data of which have been published elsewhere [ 7 ]. Significant findings in the PSG were a significantly elevated central apnea-hypopnea index (CAHI) of 17 events/hour with CSR similar to that described in adults with CSR ( Figure 1 ).…”
Section: Case Presentationmentioning
confidence: 99%